2011
DOI: 10.1038/nature10069
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite-enabled eradication of bacterial persisters by aminoglycosides

Abstract: Bacterial persistence is a state in which a sub-population of dormant cells (persisters) tolerates antibiotic treatment1-4. Bacterial persisters have been implicated in biofilms and chronic and recurrent infections5-7. Despite this clinical relevance, there are currently no viable means for eradicating persisters. Here we show that specific metabolic stimuli enable aminoglycoside killing of both Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) persisters. This potentiation is aminogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

56
955
5
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 848 publications
(1,021 citation statements)
references
References 30 publications
56
955
5
5
Order By: Relevance
“…In addition to its application as an osmolyte, mannitol and other simple sugars (and their derivatives) are being investigated as antimicrobial therapies. For example, mannitol can potentiate the activity of aminoglycosides, enhancing persister-cell eradication in vitro and the treatment of a chronic murine infection model (Allison et al, 2011). Similarly, mannose (in conjunction with other simple sugars) diminishes lung damage and potentiates standard antibiotic therapy in a murine model of P. aeruginosa pneumonia (Bucior et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its application as an osmolyte, mannitol and other simple sugars (and their derivatives) are being investigated as antimicrobial therapies. For example, mannitol can potentiate the activity of aminoglycosides, enhancing persister-cell eradication in vitro and the treatment of a chronic murine infection model (Allison et al, 2011). Similarly, mannose (in conjunction with other simple sugars) diminishes lung damage and potentiates standard antibiotic therapy in a murine model of P. aeruginosa pneumonia (Bucior et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite intensive focus on the primary drug-target interaction and its maladaptive consequences, knowledge of the endogenous mechanisms used by bacteria to resist antibiotic activity is incomplete and centred chiefly around mechanisms associated with the drug-target interaction, such as drug efflux pumps and antibiotic-and/or target-modifying enzymes 3 . However, growing evidence has implicated a broader range of physiologic factors [7][8][9][10]27 .…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have begun to revise this view with the demonstration that even non-, or slowly, replicating bacteria could be rendered sensitive to antibiotics. Studies of Escherichia coli, Staphylococcus aureus and even Mtb have shown that the activity of many antibiotics: (i) is dependent on the activity of specific metabolic pathways, (ii) differs for replicating and nonreplicating populations and (iii) can be dissociated from growth rate 7,12,27 . In Mtb, it was shown that adaptation to hypoxia was accompanied by a redirection of metabolic flux away from the TCA cycle and towards the generation of triglycerides, whose inhibition resensitized Mtb to antibiotics in absence of growth 7 .…”
Section: Discussionmentioning
confidence: 99%
“…This notion suggests extrinsic manipulation of bacterial cell metabolism may be exploited to enhance the killing efficacy of existing antibiotics. Indeed, recent work demonstrates that metabolic perturbations (102) or ROS elevation (92) can improve bactericidal lethality.…”
Section: Discussionmentioning
confidence: 99%